Biaxial failure response of composite laminates - Nayar, Dhruv (2015)
In this report, two sets of experiments are conducted. The first is biaxial testing on cruciform shaped GFRP composite laminates and the second is tensile testing on Arcan test specimens. The biaxial test aims at comparing the axial and transverse stresses under biaxial testing. The samples have different crack sizes and orientations. The tests are carried out on a new INSTRON machine. The Arcan tests aim at calculating the critical fracture toughness for modes I and II. The Arcan test jig is selected as this setup allows the extracting of fracture properties in various modes using only one shape and size of the specimen. The preparation methods for both sets of samples are described along with the curing process and curing cycles. The experiment results and data are tabulated and analyzed in detail. Finally, recommendations and scope for improvements have been highlighted. Finite element simulations using ABAQUS will also be used to obtain geometrical factors used in the calculation of the critical fracture toughness. Load-displacement curves, among other graph comparisons, are also included in the report.